2014
DOI: 10.1088/2041-8205/798/2/l27
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Extension of the Scutum-Centaurus Arm Into the Outer Second Quadrant

Abstract: Combining HI data from the Canadian Galactic Plane Survey (CGPS) and CO data from the Milky Way Imaging Scroll Painting (MWISP) project, we have identified a new segment of a spiral arm between Galactocentric radii of 15 and 19 kpc that apparently lies beyond the Outer Arm in the second Galactic quadrant. Over most of its length, the arm is 400-600 pc thick in z. The new arm appears to be the extension of the distant arm recently discovered by Dame & Thaddeus (2011) as well as the Scutum−Centaurus Arm into the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 23 publications
3
97
0
2
Order By: Relevance
“…Early HI emission surveys have first revealed that the disk of our Galaxy is warped beyond the Solar circle (e.g., Burke 1957;Kerr 1957;Burton 1988). This finding was confirmed by a series of studies in the Galactic disks traced by gaseous component (e.g., Oort et al 1958;Henderson et al 1982;Wouterloot et al 1990;Russeil 2003;Nakagawa et al 2005;Sun et al 2015), stellar component (e.g., Moitinho et al 2006;Momany et al 2006;Reylé et al 2009), as well as dust component (e.g., Drimmel & Spergel 2001;Drimmel et al 2003;Marshall et al 2006). However, our knowledge of the warp of the outer Galaxy to date is largely dependent on HI emission surveys.…”
Section: The Spiral Arm and Warp Of The Galactic Plane Traced By Co Ementioning
confidence: 57%
See 4 more Smart Citations
“…Early HI emission surveys have first revealed that the disk of our Galaxy is warped beyond the Solar circle (e.g., Burke 1957;Kerr 1957;Burton 1988). This finding was confirmed by a series of studies in the Galactic disks traced by gaseous component (e.g., Oort et al 1958;Henderson et al 1982;Wouterloot et al 1990;Russeil 2003;Nakagawa et al 2005;Sun et al 2015), stellar component (e.g., Moitinho et al 2006;Momany et al 2006;Reylé et al 2009), as well as dust component (e.g., Drimmel & Spergel 2001;Drimmel et al 2003;Marshall et al 2006). However, our knowledge of the warp of the outer Galaxy to date is largely dependent on HI emission surveys.…”
Section: The Spiral Arm and Warp Of The Galactic Plane Traced By Co Ementioning
confidence: 57%
“…The high-sensitivity data from MWISP survey will provide us a unique opportunity to systematically study the spiral structures and star-formation activities at the edge of the Milky Way. Using our new CO data of the MWISP, we have found dozens of new EOG clouds, which delineate a new segment of a spiral arm between Galactocentric radii of 15 and 19 kpc in the second Galactic quadrant (Sun et al 2015).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations